Vấn đề liên thông giữa chương trình nghề phổ thông với chương trình môn công nghệ phổ thông - Nguyen, Toàn; Nguyen, Văn Bính (Journal of Technical Education Science, 2007)
The coincidence between the content of general technology education (GTE) and gen- eral vocational education (GVE) is a weakness of education programme in Vietnam. This coincidence has been represented clearly in the programme of civil electricity industry (GVE) and electrical techniques (GTE). This has been reduced the quality of GVE at high schools and it has made students lessen the interest and waste their time. Depend on the argument of articulation, the research and experiment on articulation of “civil electric industry” programme with GTE and phisics has gotten results.